Effects of fatigue on muscle stiffness and intermittent sprinting during cycling - Ditroilo, M.; Watsford, M.; Fernandez-Pena, E.; D'Amen, G.; Lucertini, F.; de Vito, G. (Medicine & Science in Sports & Exercise, 2011)
Purpose: It was recently demonstrated that musculoarticular (MA) stiffness is related to sprint cycling performance in nonfatigued conditions. This study examined whether relatively stiffer cyclists were more effective at sprinting under fatigued conditions, as occurs during endurance cycling competitions.